2007 IEEE Conference on Computer Vision and Pattern Recognition 2007
DOI: 10.1109/cvpr.2007.383169
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Reverse Annotation for Large Scale Image Retrieval

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…On the other hand, recognition-free approaches such as Word Spotting were proposed to enable search over handwritten [3,28,30] and printed documents [4,13,26]. Pramod and Jawahar [26] use an automatic annotation approach to assign text labels to a large collection of document images.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, recognition-free approaches such as Word Spotting were proposed to enable search over handwritten [3,28,30] and printed documents [4,13,26]. Pramod and Jawahar [26] use an automatic annotation approach to assign text labels to a large collection of document images.…”
Section: Previous Workmentioning
confidence: 99%
“…Our approach has been motivated by work in word spotting in handwriting [28,30] and print [4,13,26]. Word spotting approaches usually match entire word-images.…”
Section: Recognizing Document Collec-tionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are several ways to speed up image search engines. One option is to quantize and/or index image features and retrieve them whenever necessary [2], [9], [4], [11]. Another common practice is to gain speed by sacrificing retrieval accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] focused on searching handwritten word images. Dynamic time warping (DTW) [7] was shown to be a good solution and was exploited by [9] to index a collection of 500 scanned printed books in Indian languages. The one weakness of dynamic time warping is that it is slow and hence [3] showed that locality sensitive hashing could instead be used to index and search word images rapidly within a book.…”
Section: Introductionmentioning
confidence: 99%